A facile strategy for the synthesis of block copolymers bearing an acid-cleavable junction. Issue 14 (14th April 2015) - Sui, Xin; Zhang, Zhenyu; Guan, Song; Xu, Yawei; Li, Chao; Lv, Yufeng; Chen, Aihua; Yang, Lijun; Gao, Longcheng
<x xml:space="preserve">Abstract</x> We present a facile and inexpensive approach to synthesize block copolymers bearing an acid-cleavable junction.